Automated titanium fastener vs. hand-tied knots for prosthesis fixation in infective endocarditis - Kahrovic, Amila; Angleitner, Philipp; Herkner, Harald; Werner, Paul; Poschner, Thomas; Alajbegovic, Leila; Kocher, Alfred; Ehrlich, Marek; Laufer, Günther; Andreas, Martin (Frontiers in Cardiovascular Medicine, 2024)
To date, there is no evidence regarding the safety of automated titanium fastener compared with hand-tied knots for prosthesis fixation in infective endocarditis.Between January 2016 and December 2022, a total of 220 patients requiring surgery for infective endocarditis were included in this retrospective analysis. The primary study endpoint was re-endocarditis during follow-up. The secondary study endpoints included stroke onset, allcause mortality, and a composite outcome of either re-endocarditis, stroke, or all-cause mortality during follow-up.Suture-securing with an automated titanium fastener was performed in 114 (51.8%) patients, whereas the conventional technique of hand knot-tying was used in 106 (48.2%) patients. The risk of re-endocarditis was significantly lower in the automated titanium fastener group, as shown in a multivariable proportional competing risk regression model (adjusted sub-hazard ratio 0.33, 95% confidence interval 0.11 -0.99, p = 0.048). The multivariable Cox proportional hazards regression analysis showed that the automated titanium fastener group was not associated with an increased risk of stroke-onset or attaining the composite outcome, respectively, (adjusted hazard ratio 0.54, 95% confidence interval 0.27 -1.08, p = 0.082), (adjusted hazard ratio 0.65, 95% confidence interval 0.42 -1.02, p = 0.061). Also, this group was not associated with an increased risk of all-cause mortality, as demonstrated in the multivariable Poisson regression analysis (adjusted incidence-rate ratio 1.42, 95% confidence interval 0.83 -2.42, p = 0.202).The use of automated titanium fastener device seems to be safe for infective endocarditis. Analyses of larger cohorts are required.